Holographic thermal propagator for arbitrary scale dimensions - Bajc, Borut (2023)
Using the AdS/CFT correspondence we model the behaviour of the two-pointcorrelator of an operator with arbitrary scale dimension Delta in arbitrary spacetime dimensiond for small but non-zero temperature. The obtained propagator coincides in the lowtemperature regime with the known result for d = 4 for large Delta at the order T^d as well aswith the T^d and T^2d terms of the exact all order result for d = 2. Furthermore, for arbitraryd we explicitly write down the expression for the order T^d of the propagator for arbitraryDelta, and present a conjecture for the order T^2d in the large Delta limit.